2018
DOI: 10.1093/jee/toy060
|View full text |Cite
|
Sign up to set email alerts
|

Pyraclostrobin Impairs Energetic Mitochondrial Metabolism and Productive Performance of Silkworm (Lepidoptera: Bombycidae) Caterpillars

Abstract: Silkworm cocoon production has been reduced due to a number of problems other than those inherent in sericulture, such as diseases, malnutrition, and inappropriate management. The use of pesticides in areas surrounding mulberry fields can contaminate these plants and consequently harm caterpillars. The aim of this study was to evaluate whether the application of the fungicide pyraclostrobin in mulberry plants interferes with the mitochondrial bioenergetics and the productive performance of silkworms. Mulberry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…We found that pyraclostrobin acts as a respiratory chain inhibitor, affecting mitochondrial bioenergetics in the honey bee thorax. This is consistent with what was previously found in another domesticated insect, the silkworm ( Bombyx mori ; Nicodemo et al 2018). Mitochondrial oxidative phosphorylation is the primary process by which aerobic cells produce ATP by esterification of ADP with inorganic phosphate.…”
Section: Discussionsupporting
confidence: 93%
“…We found that pyraclostrobin acts as a respiratory chain inhibitor, affecting mitochondrial bioenergetics in the honey bee thorax. This is consistent with what was previously found in another domesticated insect, the silkworm ( Bombyx mori ; Nicodemo et al 2018). Mitochondrial oxidative phosphorylation is the primary process by which aerobic cells produce ATP by esterification of ADP with inorganic phosphate.…”
Section: Discussionsupporting
confidence: 93%
“…This research gap is noteworthy since some experiments show negative effects of herbicides on Lepidoptera performance, including reduced survival or wing size [18][19][20] , adult emergence 21 and sex-pheromone production 22 . Similar studies, mainly on commercial (Bombyx mori L.) and pest (Spodoptera litura F.) lepidopteran species, have found that fungicides can also reduce larval survival, pupal weight or adult longevity 23,24 . Moreover, fungicides synergize the action of insecticides by inhibiting cytochrome P450 enzymes in honey bees [25][26][27][28] .…”
Section: Larval Pesticide Exposure Impacts Monarch Butterfly Performamentioning
confidence: 74%
“…4D,E), perhaps because larval mitochondria are heavily involved in protein synthesis (Nicodemo et al. 2018) or because HIF activation affects DNA methylation across the genome (Choudhry and Harris 2018). Reduced growth rate should have a negative effect on larval fitness by prolonging exposure to factors such as adverse weather, parasitoids, predators, host plant depletion, and seasonal drying of the habitat (Lampert and Trubetskova 1996; Van Nouhuys and Hanski 1999; Whitney‐Johnson et al.…”
Section: Discussionmentioning
confidence: 99%